2003
DOI: 10.1191/0269215503cr604oa
|View full text |Cite
|
Sign up to set email alerts
|

Use of unconventional therapies by individuals with multiple sclerosis

Abstract: The prevalence of CAM use in this population warrants more research on the efficacy and safety of these therapies, especially those with high usage or high efficacy ratings, such as herbs, chiropractic manipulation and massage, but for which there is little or no research evidence for efficacy or safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
133
7
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(168 citation statements)
references
References 9 publications
23
133
7
5
Order By: Relevance
“…19 Esmonde and Andrew, Nayak et al, and Berkman et al also reported an improvement of sleep quality in patients with MS who did PMRT in their studies. [33][34][35] When the relationship between the patients' sleep quality and their mean scores from fatigue scales were evaluated after PMRT, a positively significant relationship was observed between the mean scores of fatigue severity scale and the mean scores of subjective sleep quality, sleep disorder, daytime dysfunction, and global sleep quality after PMRT. Patients' fatigue level increased as their sleep quality deteriorated.…”
Section: Discussionmentioning
confidence: 99%
“…19 Esmonde and Andrew, Nayak et al, and Berkman et al also reported an improvement of sleep quality in patients with MS who did PMRT in their studies. [33][34][35] When the relationship between the patients' sleep quality and their mean scores from fatigue scales were evaluated after PMRT, a positively significant relationship was observed between the mean scores of fatigue severity scale and the mean scores of subjective sleep quality, sleep disorder, daytime dysfunction, and global sleep quality after PMRT. Patients' fatigue level increased as their sleep quality deteriorated.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a growing number of individuals have turned to mind-body therapies-a specific exercise regimen including yoga, mediation, relaxation techniques, breath work, visual imagery, hypnotherapy, and biofeedback-to manage symptoms of MS. [27][28][29][30][31][32][33] For example, Yadav and colleagues 32 conducted a survey with 1110 patients with MS. Thirty-two percent reported both highly perceived psychological and physical benefits to using mind-body modalities, such as yoga, meditation, relaxation techniques, and breathing. In another study, Nayek et al 30 gathered data from 11,600 individuals with MS and found that 57.1% of the responding sample had used at least one form of complementary and alternative medicine (CAM), citing a general preference for alternative mind-body therapies.…”
Section: Mind-body Therapies For Msmentioning
confidence: 99%
“…In another study, Nayek et al 30 gathered data from 11,600 individuals with MS and found that 57.1% of the responding sample had used at least one form of complementary and alternative medicine (CAM), citing a general preference for alternative mind-body therapies. Similarly, Esmond and Long 33 examined the use of six CAM mindbody modalities for MS symptom management (i.e., reflexology, massage, yoga, relaxation and meditation, acupuncture, and aromatherapy).…”
Section: Mind-body Therapies For Msmentioning
confidence: 99%
“…Indeed, depending on the sample, estimates regarding the prevalence of CAM use in people with MS range from approximately 33 [13] to 66 percent [12,20]. People with MS have credited CAM with improving their quality of life and reducing their MS-related symptoms [12,[20][21]. In one investigation of the perceived effectiveness of CAM treatments, substantial proportions of participants with MS believed that CAM services slowed disease progression and induced remission [22].…”
Section: Introductionmentioning
confidence: 99%
“…In light of disease-related statistical predictors, CAM use appears more likely among those with more severe symptoms and a more prolonged course [22]. One study observed that patients with secondary progressive MS (SPMS) were more likely to report CAM use than patients with other subtypes of the disease [21]. Overall, CAM use appears to be highly prevalent and highly valued by persons with MS.…”
Section: Introductionmentioning
confidence: 99%